Етапи інституалізації судових експертиз - Щербаковський, М. Г.; Shcherbakovskyi, M. H.; Михайло Щербаковський (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 124–131, 2016)
Розглянуто етапи розвитку інституту судової експертизи з моменту її першої згадки у 16 ст. до наших днів. Виділено п’ять етапів становлення інституту судової експертизи. Підставою періодизації обрано правову регламентацію залучення експерта, виникнення спеціалізованих експертних установ і формування наукових основ теорії судових експертиз.

Studies of the history of origin and establishment of procedural institution of forensic expertise are necessary for the formation of this scientific field, determining its nature, essence, theoretical significance and practical orientation in forensic activities. The author distinguishes five stages of the development of the institution of forensic expertise. The first stage – is from the XVI century, when forensic investigation has been first mentioned, up to 1864, when the expertise was legislated in criminal proceedings. The second stage – 1864–1913 – is characterized by the accumulation of empirical data, the emergence of new types of expertise. The third stage – 1913 – late 1950s, the beginning of which is the creation of the state forensic institutions, the employees of which performed the examinations on a professional basis; at this stage the rights of an expert have been consolidated in legislation, there was the development of theoretical foundations of various types of expertise, general scientific basis of expert research were formed. The fourth stage – the end of 1950s – 2007 – is linked to the introduction of the new procedural law, which regulates the procedure of conducting examinations, the rights and duties of its participants; the foundations of a particular scientific field of knowledge – the theory of judicial expertise have been laid and developed. The fifth stage – from 2007 up to the present day – is characterized by the further development of the theory of judicial expertise in terms of new adversarial criminal procedure.

Рассмотрены этапы развития института судебной экспертизы с момента ее первого упоминания в 16 веке до наших дней. Выделено пять этапов становления института судебной экспертизы. Основанием периодизации выбраны правовая регламентация привлечения эксперта, возникновение специализированных экспертных учреждений и формирование научных основ теории судебных экспертиз.
Этапы институализации судебных экспертиз
Stages of institutionalization of forensic expertise
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; судова експертиза; етапи розвитку; Історія. History. История; судебная экспертиза; этапы развития; экспертные учреждения; експертні установи; forensic expertise; stages of development; expert institutions